2013
DOI: 10.3109/10428194.2013.778407
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and extent of CD30 expression in diffuse large B-cell lymphoma and its relation to clinical and biologic factors: a retrospective study of 167 cases

Abstract: Previous studies have suggested that CD30 may be expressed in diffuse large B-cell lymphomas (DLBCLs). However, the prevalence of CD30 + DLBCLs and extent of CD30 expression within an individual tumor have not been fully evaluated. The aim of this study was to determine the frequency and extent of CD30 expression in DLBCLs, and explore possible relationships between CD30 expression and clinical and biologic variables. We retrospectively identified and analyzed 167 cases of CD30 + DLBCLs from our pathology arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 25 publications
2
21
2
Order By: Relevance
“…Our findings are consistent with those of the International DLBCL Rituximab‐CHOP Consortium Program Study, who found that 14% of 903 cases of de novo DLBCL in TMA exhibited CD30 expression in 20% or more tumour cells (Hu et al , ); and The Cleveland Clinic, who reported that 10% of 94 de novo DLBCL cases in TMA contained 20% or more CD30+ tumour cells (Hill et al , ). These findings differ from the study by Campuzano‐Zuluaga et al (), who found that 21% of de novo DLBCL cases contained 20% or more CD30+ tumour cells. This could be due to variations in study design and patient selection and might reflect differences in underlying tumour biology.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are consistent with those of the International DLBCL Rituximab‐CHOP Consortium Program Study, who found that 14% of 903 cases of de novo DLBCL in TMA exhibited CD30 expression in 20% or more tumour cells (Hu et al , ); and The Cleveland Clinic, who reported that 10% of 94 de novo DLBCL cases in TMA contained 20% or more CD30+ tumour cells (Hill et al , ). These findings differ from the study by Campuzano‐Zuluaga et al (), who found that 21% of de novo DLBCL cases contained 20% or more CD30+ tumour cells. This could be due to variations in study design and patient selection and might reflect differences in underlying tumour biology.…”
Section: Discussioncontrasting
confidence: 99%
“…32 Assessing responses to brentuximab vedotin by cell of origin of DLBCL would be an interesting exploratory analysis, although CD30 expression does not clearly correspond to the GCB or the ABC subtype of DLBCL. [15][16][17][18] Other limitations of this study are the lack of a comparator arm, absence of central review of response, and lack of analysis of response by other potentially important prognostic markers, such as Bcl-2 or c-Myc. We also cannot exclude the possibility that relapsed CD30…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] CD30 is expressed in a variety of malignancies 13,14 and is present in 14% to 25% of DLBCL patients, depending on the cutoff used to assign positivity. [15][16][17] Hu et al reported a unique gene expression profile for de novo DLBCL expressing CD30 in greater than 20% of cells. 15 Although this study suggested that CD30 expression imparts a more favorable prognosis with first-line R-CHOP therapy, other studies have not universally confirmed this finding and the prognostic implications of CD30 expression at relapse are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, they did not mention the status of MYC and BCL2 expression. However, Campuzano-Zuluaga et al13 and Hao X et al15 argued that CD30 expression was positively associated with BCL2 expression and inferior outcome. Some patients with EBV+ DLBCL were mixed in their cohort.…”
Section: Discussionmentioning
confidence: 99%